Purification of Peroxisomes in a Preformed Iodixanol Gradient in a Fixed-Angle Rotor - John Graham (The Scientific World Journal)
In iodixanol, peroxisomes are the densest organelle in the light mitochondrial fraction and are therefore easily separated from the other components (lysosomes, mitochondria, etc.) in a preformed isosmotic continuous gradient. The resolution of the peroxisomes is far superior than that in sucrose and, unlike in Percoll® there is no contamination from endoplasmic reticulum.